Implementation and development of early intervention in psychosis services in Italy: a national survey promoted by the Associazione Italiana Interventi Precoci nelle Psicosi. Issue 1 (29th September 2015) - Cocchi, Angelo; Cavicchini, Anna; Collavo, Marzia; Ghio, Lucio; Macchi, Sara; Meneghelli, Anna; Preti, Antonio
Abstract: Aim: This is the first comprehensive, nationwide survey aimed at collecting evidence about the process of implementation and development of early intervention in psychosis (EIP) services (EIPs) in Italy, following the establishment of the pilot program 'Programma 2000' in 1999 and the publishing of the Italian National Guidelines in 2007. This survey covers all the Departments of Mental Health (DMHs) operating in Italy in 2013. Methods: Using a purpose‐designed form to assess EIP implementation, all directors of public mental health services for adults throughout Italy ( n  = 216) were asked to provide information about the activities of EIP‐relevant local services. The initial delivery was followed by a request for a prompt response. Results: Out of 216 enquired DMHs, 103 provided computable answers to the survey (response rate = 48%). Among responders, 45 (44%) reported the implementation of EIP (one out of five DMHs operating in Italy). About a half of the active EIPs also targeted patients at ultra‐high risk of psychosis ( n  = 27). Strict application of guidelines related to drug prescription was reported in 35% of EIPs. Conversely, 90% provided some kind of structured psychotherapy and psychoeducation. Among EIPs, a minority reported willingness to provide initial assessment/contact at the patient's home. Conclusion: Albeit slowly, the implementation of EIP is spreading throughout the Italian public network of mental health. There is still a wide variability in the distribution of EIP services across the Italian territory. Further efforts are necessary to stimulate policy endorsement and resource allocation, as well as to support the poorest zones.